Co-fabrication of chitosan and epoxy photoresist to form microwell arrays with permeable hydrogel bottoms. (January 2016) - Ornoff, Douglas M.; Wang, Yuli; Proctor, Angela; Shah, Akash S.; Allbritton, Nancy L.
Abstract: Microfabrication technology offers the potential to create biological platforms with customizable patterns and surface chemistries, allowing precise control over the biochemical microenvironment to which a cell or group of cells is exposed. However, most microfabricated platforms grow cells on impermeable surfaces. This report describes the co-fabrication of a micropatterned epoxy photoresist film with a chitosan film to create a freestanding array of permeable, hydrogel-bottomed microwells. These films possess optical properties ideal for microscopy applications, and the chitosan layers are semi-permeable with a molecular exclusion of 9.9 ± 2.1 kDa. By seeding cells into the microwells, overlaying inert mineral oil, and supplying media via the bottom surface, this hybrid film permits cells to be physically isolated from one another but maintained in culture for at least 4 days. Arrays co-fabricated using these materials reduce both large-molecular-weight biochemical crosstalk between cells and mixing of different clonal populations, and will enable high-throughput studies of cellular heterogeneity with increased ability to customize dynamic interrogations compared to materials in currently available technologies.